Multidrug‐Resistant stx1 Harboring Escherichia coli from Meat Shop and Fast Food. Issue 4 (22nd September 2013) - Pavithra, M; Ghosh, Asit Ranjan
Abstract E scherichia coli have public health impact on humans by causing gastroenteritis including hemorrhagic colitis and hemolytic uremic syndrome. A total of 215 samples collected from fast foods, swabs from meat shops and fish markets were examined. Thirty‐six samples (16.74%) were identified as E. coli with various serogroups like O8, O19, O22, O41, O60, O101, O116 and O147, respectively. Only nine (25%) E. coli possessed the gene encoding shiga toxin (stx 1). Isolated E. coli were multidrug‐resistant with complete resistance to fluroquinolones (ciprofloxacin, norfloxacin, ofloxacin, and lomefloxacin respectively). Isolation of stx 1 bearing E. coli with multidrug resistance from fast food and meat sources is a clear indication of environmental contamination and is a matter of public health concern. Practical Application Detection of diarrheogenic serogroups of stx 1 harboring Escherichia coli with multidrug resistance in fast foods and meat shops is applicable in creating awareness among public about the unhygienic practices followed in the fast food centers and retail meat shops and also the improper disposal of fecal and antibiotic wastes, which is the cause for such contaminations. This study also insists the need of health education and hygienic practice for the food handlers.